A COMPARATIVE ANALYSIS ON: THE SIMILARITIES AND DIFFERENCES OF THE THE PHILOSOPHICAL PERSPECTIVE AND METHODOLOGY ADOPTED IN TWO DIFFERENT QUALITATIVE RESEARCHES - Adi Suryani (JURNAL SOSIAL HUMANIORA (JSH), 2013)
Qualitative research has substantial philosophical dimension difference from quantitative research. Instead of adopting positivism, qualitative research focuses on more interpretivism and Relativism philosophical perspectives. From these two analyzed researches (Local responses to decentralization policy in Indonesia and Two sides of the same coin: Modernity and tradition in Islamic Education in Indonesia), we learn that both of them put their research stance on interpretivism and constructionism, eventhough they use different methodology. This different methodology emerges because of different focus, goals (objectives), and questions of the research. The Two sides of the same coin uses ethnographic method, while The Local responses adopts interview and official document analysis. Because The Two sides of the same coin adopts ethnographic methodology, it takes one Pesantren as its research site and research it as one whole system. Meanwhile, The Local responses takes six secondary school students to be interviewed. Thus, qualitative researches can be vary depending on research goals (objectives), focus, and problems (questions.